2013
DOI: 10.1089/pho.2012.3379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical and Antimicrobial Effects of the Er:YAG Laser or Topical Gaseous Ozone as Adjuncts to Initial Periodontal Therapy

Abstract: Although statistically nonsignificant, the fact that the obligate anaerobic change was mostly observed in the SRP+Er:YAG laser group, and a similar decrease was noted in the SRP+topical gaseous ozone group, shows that ozone has an antimicrobial effect equivalent to that of the Er:YAG laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 22 publications
5
45
0
12
Order By: Relevance
“…In addition, our data also support the findings of Yilmaz et al. (, ), who observed that positive changes in clinical parameters such as attachment gain and PD reduction were significantly greater in the ERL + SRP group than the SRP group. Likewise, Saglam et al.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our data also support the findings of Yilmaz et al. (, ), who observed that positive changes in clinical parameters such as attachment gain and PD reduction were significantly greater in the ERL + SRP group than the SRP group. Likewise, Saglam et al.…”
Section: Discussionsupporting
confidence: 91%
“…, Yilmaz et al. , ). The smoking rate varied among selected studies, with five including non‐smoking populations.…”
Section: Resultsmentioning
confidence: 98%
“… There is substantial heterogeneity between studies, in design, selection of laser parameters and length of study, all of which limit the number of studies that can be entered into a meta‐analysis. Differences in average post‐treatment probing depth reduction, control vs. test groups, ranged from 0.07 mm at 3 months to 0.16 mm at 6 months (Table ) – a clinically insignificant difference at both time intervals. Differences in average post‐treatment gains in clinical attachment level, control vs. test groups, ranged from 0.08 mm at 3 months to 0.29 mm at 6 months (Table ) – clinically insignificant at both time intervals. Differences in average post‐treatment reduction of bleeding on probing, control vs. test groups, were approximately 0% at 3 months but decreased to 3% at 6 months (Table ) – a clinically insignificant difference at both time intervals. As one of the primary rationales for incorporation of lasers into a periodontal treatment regimen is the purported antimicrobial effect, it is disappointing that nine of 19 studies did not measure this parameter. Of the remaining 10 studies, eight demonstrated no significant difference between control and test groups ; one favored the adjunctive use of the laser with scaling and root planing ; and one showed a significant reduction in T. forsythia following use of the laser as a monotherapy ; and in one study only the scaling and root planing group produced a significant reduction in levels of spirochetes and motile rods vs. baseline . Overall, one must conclude that the laser, at best, is equivalent to scaling and root planing and has no added clinical benefit regarding reduction in subgingival microbial loads. There is no evidence that the Er:YAG laser, used as a monotherapy or adjunctive to scaling and root planing, is capable of “sterilizing” a periodontal pocket (Table ). Currently, there is no evidence showing that use of the Er:YAG laser in treatment of periodontitis has a beneficial impact on the levels of inflammatory cytokines as only two conflicting studies have addressed the subject. Currently, there is no consistent evidence supporting routine use of the Er:YAG laser in the treatment of periodontitis, either as an alternative monotherapy or adjunctive to traditional scaling and root planing . …”
Section: Summary Of Er:yag Laser and Treatment Of Periodontitismentioning
confidence: 99%